The Role of Omega-3/Omega-6 Ratio on Appetite in Pulmonary Multidrug-Resistant Tuberculosis Patients - Fattrias Handayani Jayaatmaja; Nurul Ratna Mutu Manikam; Inge Permadhi; Neni Sawitri; Budi Rahayu; Adityo Wibowo; Fariz Nurwidya (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: Tumour necrosis factor-alpha (TNF-α) levels, pro-inflammatory cytokines that suppress appetite, were discovered to be much higher in multidrug-resistant tuberculosis (MDR-TB) than in drug-sensitive TB. Research on the omega-3/omega-6 (êž·-3/êž·-6) polyunsaturated fatty acids (PUFAs) intake, which can support appetite in patients with MDR-TB, has never been performed. This study aimed to examine the relationship between êž·-3/êž·-6 PUFAs intake ratio and appetite mediated by TNF-α in pulmonary MDR-TB patients. Methods: This was a cross-sectional study conducted on 46 male and female adults with MDR-TB undergoing intensive phase therapy. Data were collected through questionnaires, 1x24 hours food recall, anthropometric measurements, 100 mm visual analogue appetite scale, and venous blood collection. Results: Correlation analysis used the Pearson and Spearman tests. The findings revealed the ratio of êž·-3/êž·-6 PUFAs intake of 0.11 ± 0.05, the median value of TNF-α 7.49(1.66-447.62) pg/mL, and an average appetite of 58.72 ± 26.7. There was no relationship between êž·-3/êž·-6 PUFAs intake ratio and TNF-α (r = 0.016; p = 0.91), likewise between êž·-3/êž·-6 PUFAs intake ratio with appetite (r = -0.1; p = 0.54), but there was a relationship between TNF-α and appetite (r = 0.031; p = 0.04). Conclusion: There was no relationship between êž·-3/êž·-6 PUFAs intake ratio and TNF-α and appetite in pulmonary MDR-TB patients. However, there was a relationship between TNF-α and appetite. This study is the first to determine the correlation between êž·-3/êž·-6 PUFAs intake ratio and appetite in pulmonary MDR-TB patients.